2007
DOI: 10.1155/2007/597123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of USA300 Colonization or Infection and Associated Variables During an Outbreak of Community‐Associated Methicillin‐Resistant Staphylococcus aureus in a Marginalized Urban Population

Abstract: Ongoing efforts to promote the appropriate treatment of skin infections in this population are warranted. The association of USA300 colonization or infection and drug use with sexual partners suggest a role for sexual transmission of the USA300 strain of MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Subsequently, most reports describing the MRSA strains that either colonized or caused invasive infections among individuals in the United States have used the USA nomenclature to report strain types (29,30,32). The MRSA strain type USA300, which initially was seen primarily as a cause of community-associated skin and soft tissue infections (18), has now been reported from invasive infections in the United States and in many countries around the world (2,19,23,29,31,40,43,46,50). Although PFGE typing continues to be of value for epidemiologic studies of MRSA strains (32), spa typing data, often reported in conjunction with SCCmec typing data, are used with increasing frequency around the world for MRSA strain identification (20,24).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, most reports describing the MRSA strains that either colonized or caused invasive infections among individuals in the United States have used the USA nomenclature to report strain types (29,30,32). The MRSA strain type USA300, which initially was seen primarily as a cause of community-associated skin and soft tissue infections (18), has now been reported from invasive infections in the United States and in many countries around the world (2,19,23,29,31,40,43,46,50). Although PFGE typing continues to be of value for epidemiologic studies of MRSA strains (32), spa typing data, often reported in conjunction with SCCmec typing data, are used with increasing frequency around the world for MRSA strain identification (20,24).…”
Section: Discussionmentioning
confidence: 99%
“…Volatile materials were removed under a flow of N 2 (g). The resulting crude solid was resuspended in acetone to dissolve any residual dimethylalkylamine and vacuum filtered to yield the solid amphiphile product (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Details for each product and analytical data are provided in Supporting information.…”
Section: Synthesis Of 1-10: General Protocol Amentioning
confidence: 99%
“…[1][2][3][4][5] In addition, the production of novel antimicrobials continues to decrease, primarily due to low financial return. 5,6 This combination of circumstances has contributed to the increasing prevalence of antimicrobial-resistant infections (ARIs), especially in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Of particular concern in Canada are the outbreaks of C. difficile-associated disease with increased morbidity and mortality that have occurred in Quebec, 8,11 the emergence of community-acquired MRSA 9 and the increasing number of hospital-acquired MRSA infections. 12 In a study conducted in 11 emergency departments in the United States in August 2004, 78% of S. aureus skin and soft-tissue infections were due to community-acquired MRSA.…”
Section: Introductionmentioning
confidence: 99%